Uncovering the Provenance of “Orphaned” Objects - Haoyang Zhao (Asian Studies)
In recent years, scattered pages of the coloured version of Huangchao liqi tushi have been found in several public institutions outside China and even on the art market. The discovery of pages bearing the Yuanmingyuan seal has led to them being associated with the looting of Yuanmingyuan in 1860. However, as commonly encountered in provenance research, a thorough analysis of the available archives indicates that portions of pages held in various institutions were acquired from unrelated individuals or dealers at different times, without substantial evidence linking them directly to the looting of Yuanmingyuan or to soldiers involved in the looting. Consequently, it is not possible to definitively establish their Yuanmingyuan provenance. Facing these challenges, this study employs methods beyond the traditional archival research approach, demonstrating how additional insights can be derived from checking indirect archives and marks on the reverse of pages. More importantly, the study showcases how an art historical understanding of the material can offer new perspectives, shifting the focus from searching for provenance documents of individual portions to connecting portions without records to those with more solid evidence, considering the possibility that direct provenance records may never have existed.